2023
DOI: 10.38138/jmdr/v9i1.23.4
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Fresh Fruit Extracts and Commercially Available Fruit Extracts on the Growth of Streptococcus mutans — An In Vitro Study

P K Asmin,
Fareed Nusrath

Abstract: Resistance of antibiotics towards pathogenic microorganisms has led to the continuous search of natural plant products as a potential alternative for synthetic antibiotic agents. Many plant produces have shown promising results towards this end. This has led to commercialization and packaging of plant produce especially fruits. However, much research needs to be conducted to assess the potential benefits of commercially available plant produce compared to the natural ones. Consumable food items have both posit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Many studies have found that fruit juice components have antimicrobial and anticarcinogenic properties in humans. These characteristics help to prevent chronic inflammatory diseases, cancer, and cardiovascular disease (Asmin andNusrath, 2023, García-Manríquez et al, 2023). Fruit juice and smoothies have grown in popularity as people become more aware of their health benefits.…”
Section: Introductionmentioning
confidence: 99%
“…Many studies have found that fruit juice components have antimicrobial and anticarcinogenic properties in humans. These characteristics help to prevent chronic inflammatory diseases, cancer, and cardiovascular disease (Asmin andNusrath, 2023, García-Manríquez et al, 2023). Fruit juice and smoothies have grown in popularity as people become more aware of their health benefits.…”
Section: Introductionmentioning
confidence: 99%